Tardiness Increases in Winter: Evidence for Annual Rhythms in Humans. Issue 6 (December 2019) - Zerbini, Giulia; van der Vinne, Vincent; Otto, Lana K. M.; Monecke, Stefanie; Kantermann, Thomas; Merrow, Martha
Annual rhythms in humans have been described for a limited number of behavioral and physiological parameters. The aim of this study was to investigate time-of-year variations in late arrivals, sick leaves, dismissals from class (attendance), and grades (performance). Data were collected in Dutch high school students across 4 academic years (indicators of attendance in about 1700 students; grades in about 200 students). Absenteeism showed a seasonal variation, with a peak in winter, which was more strongly associated with photoperiod (number of hours of daylight) compared with other factors assessed (e.g., weather conditions). Grades also varied with time of year, albeit differently across the 4 years. The observed time-of-year variation in the number of sick leaves was in accordance with the literature on the seasonality of infectious diseases (e.g., influenza usually breaks out in winter). The winter peak in late arrivals was unexpected and requires more research. Our findings could be relevant for a seasonal adaptation of school schedules and working environments (e.g., later school and work hours in winter, especially at higher latitudes where seasonal differences in photoperiod are more pronounced).